2020
DOI: 10.1093/jalm/jfaa098
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Tests and Outcome for Patients with Coronavirus Disease 2019: A Systematic Review and Meta-Analysis

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (COVID-19) poses substantial challenges for health care systems. With a vastly expanding amount of publications on COVID-19, clinicians need evidence synthesis to produce guidance for handling patients with COVID-19. In this systematic review and meta-analysis, we examine which routine laboratory tests are associated with severe COVID-19 disease. Content PubMed (Medli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 45 publications
2
44
2
Order By: Relevance
“…Li et al [12] and our study showed an increased hemoglobin in COVID-19 positive patients, which is not in accordance with a lowered hemoglobin in patients with severe COVID-19 disease reported by two meta-analyses. [8,16] In our data, the median hemoglobin was 13.5 g/dL, which did not much differ from Li's data. [12] In several other trials assessing the severity of disease and blood patterns, hemoglobin was shown to be below normal ranges.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…Li et al [12] and our study showed an increased hemoglobin in COVID-19 positive patients, which is not in accordance with a lowered hemoglobin in patients with severe COVID-19 disease reported by two meta-analyses. [8,16] In our data, the median hemoglobin was 13.5 g/dL, which did not much differ from Li's data. [12] In several other trials assessing the severity of disease and blood patterns, hemoglobin was shown to be below normal ranges.…”
Section: Discussioncontrasting
confidence: 46%
“…[12] In several other trials assessing the severity of disease and blood patterns, hemoglobin was shown to be below normal ranges. [8,9,16] It can only be hypothesized why our cohort presented with a comparably high level of hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other clinical reports showed that severe diseases among COVID-19 patients were associated with higher white blood cell and neutrophil counts, C-reactive protein, lactate dehydrogenase, D-dimer, and aspartate aminotransferase [26,27]. Additionally, CT imaging displayed ground-glass opacification patterns (80%) as well as bilateral involvement (69%).…”
Section: Clinical Coursementioning
confidence: 90%
“…This finding does not prove the direct association, and the observed finding can be due to other confounding variables or poor patient detection in tropical countries. A systematic review shows that six studies described low hemoglobin in patients with COVID-19, while four studies found that all patients had hemoglobin within the reference interval (69) . However, a limitation for this alteration is that most studies reported laboratory analysis from the patients at admission.…”
Section: Interrelations Between Prolonged Hospitalization Weight Losmentioning
confidence: 99%